2012
DOI: 10.1002/app.38416
|View full text |Cite
|
Sign up to set email alerts
|

Foaming behavior of microcellular foam polypropylene/modified nano calcium carbonate composites

Abstract: A new process was used to prepare microcellular foams with supercritical carbon dioxide as the physical foaming agent in a batch. The foaming temperature range of the new process was about five times broader than that of the conventional one. Characterization of the cellular structure of the original polypropylene (PP) and PP/nano‐CaCO3 (nanocomposites) foams was conducted to reveal the effects of the blend composition and processing conditions. The results show that the cellular structure of the PP foams was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 23 publications
(30 reference statements)
0
65
0
Order By: Relevance
“…These advantages include a light weight, higher impact strength1, higher fatigue life and cost reduction2, higher sound insulation3. Because of these excellent properties, they have been used in many applications, including thermal and sound insulators, packaging, electromagnetic shielding materials, structural components and medical devices45.…”
mentioning
confidence: 99%
“…These advantages include a light weight, higher impact strength1, higher fatigue life and cost reduction2, higher sound insulation3. Because of these excellent properties, they have been used in many applications, including thermal and sound insulators, packaging, electromagnetic shielding materials, structural components and medical devices45.…”
mentioning
confidence: 99%
“…The cells of the nanocomposites were always uniform. Compared with the conventional process, the new one had a much broader temperature range (42).…”
Section: Thermal Sound and Electrical Insulationmentioning
confidence: 99%
“…Talc is usually used as a nucleating agent in many types of foams. However, it was reported that some nanofillers like nanoclay (18), nanosilica (19) and nano-calcium carbonate (20) had better nucleation efficiency than talc in PP foams. Nanofiller nucleating agents can simultaneously improve the melt strength of PP and thus suppress cell coalescence (19,21).…”
Section: Introductionmentioning
confidence: 99%